Transtibial prosthetic socket pistoning: Static evaluation of Seal-In® X5 and Dermo® Liner using motion analysis system - Gholizadeh, Hossein; Abu Osman, Noor Azuan; Kamyab, Mojtaba; Eshraghi, Arezoo; Wan Abas, Wan Abu Bakar; Azam, M.N. (Elsevier, 2012)
Background: The method of attachment of prosthesis to the residual limb (suspension) and socket fitting is a critical issue in the process of providing an amputee with prosthesis. Different suspension methods try to minimize the pistoning movement inside the socket. The Seal-In® X5 and Dermo® Liner by Ossur are new suspension liners that intend to reduce pistoning between the socket and liner. Since the effects of these new liners on suspension are unclear, the objective of this study was to compare the pistoning effect of Seal-In® X5 and Dermo® Liner by using Vicon Motion System.